Pregnancy outcomes of patients with acute fatty liver of pregnancy: a case control study - Lingzhi Chang; Ming Wang; Haixia Liu; Qinghua Meng; Hongwei Yu; Yu-mei Wu; Yunxia Zhu (BMC, 2020)
Abstract Background Limited data exists regarding the pregnancy and infant outcomes of Acute Fatty Liver of Pregnancy (AFLP). Methods Retrospectively collected mothers with AFLP and mothers without AFLP in our center from 1/2008 to 6/2018. The primary assessment was to analyze and compare the frequency of negative maternal and fetal outcomes. The secondary assessment was to investigate the role of intrauterine balloon tamponade in reducing negative maternal outcomes. Results Compared to 220 matched mothers, 55 AFLP mothers were younger (P < 0.001), with fewer pregnancies (P = 0.033), complicated with more pregnancy induced hypertension (P < 0.001), twins(P = 0.002), fetal growth restriction (P = 0.044) and male fetus (P < 0.001). 3 (5.5%) of AFLP patients were diagnosed in the postpartum period. Mean gestational week of AFLP diagnosis was 35.25 ± 5.80 weeks. Jaundice (89.1%), nausea or vomiting (58.2%), anorexia (49.1%), fatigue (45.5%) and polydipsia (30.9%) were the main prodromal symptoms. The median duration from diagnosis to delivery was 1.55 ± 4.62 days and 75% (39/52) pregnancy were terminated the pregnancy at the day of diagnosis. 78.8% (41/52) patients received cesarean section, 53.6% (22/41) of which received preventive plasma transfusion before surgery and no one received artificial liver support during the treatment. In comparison, higher frequency of 16 maternal complications, severe negative outcomes (27.3% vs. 0.9%) and newborn asphyxia (24.6% vs.0.9%) were observed in AFLP population. 3 mothers (mortality rates: 5.5%) died of multiple organ system failure and 6 fetus/infants (death rates: 9.8%) died of distress. When compared to those without negative outcomes, patients with negative fetal outcomes were younger (P = 0.042), had more singleton rates (p = 0.041), increased mean value of ALT(P = 0.011) and T-Bilirubin (P = 0.014), decreased prothrombin activity (P = 0.011). Although no statistical significance for the small sample size, there were less refractory postpartum hemorrhage (0% vs.31.3%), hysterectomy (0% vs.12.5%), negative maternal outcomes (16.7% vs.56.3%) in patients underwent intrauterine balloon tamponade when postpartum hemorrhage exceeded 500 ml. Conclusions Several symptoms were found to be the main prodromal symptoms of AFLP. Higher frequency of adverse maternal and fetal outcomes was observed in mothers with AFLP than mothers without AFLP. We found five potential risk factors of negative fetal outcomes.